2015
DOI: 10.3835/plantgenome2014.09.0051
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Granule‐Bound Starch Synthase I Gene in Chenopodium

Abstract: Chenopodium L. is a relatively under-studied genus that includes the cultivated seed crop quinoa (C. quinoa Willd.). Quinoa is an allotetraploid (2n = 4x = 36, AABB genomes) that is cultivated by subsistence farmers and commercial growers in the Andean regions of South America. Approximately 60% of a quinoa seed is starch, a glucose polymer that is an important carbohydrate energy source in the human diet. Seed starch is normally composed of amylose and amylopectin in a 1:3 ratio. The accumulation of the amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 79 publications
2
25
0
Order By: Relevance
“…However, Arabidopsis is a diploid species and quinoa an allotetraploid. The tetraploid quinoa genome was formed upon hybridisation of two diploid subgenomes; the A-genome from Chenopodium pallidicaule and the B-genome from Chenopodium suecicum (Brown et al 2015;Štorchová et al 2014;Walsh et al 2015). The hybridisation event occurred an estimated 3.3-3.6 million years ago (Jarvis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, Arabidopsis is a diploid species and quinoa an allotetraploid. The tetraploid quinoa genome was formed upon hybridisation of two diploid subgenomes; the A-genome from Chenopodium pallidicaule and the B-genome from Chenopodium suecicum (Brown et al 2015;Štorchová et al 2014;Walsh et al 2015). The hybridisation event occurred an estimated 3.3-3.6 million years ago (Jarvis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The approximate content of both amylose and amylopectin was analysed by staining with Lugol's I 2 –KI Stain (0.1 g resublimated iodine and 0.2 g KI dissolved in 30 ml distilled water) following the protocol developed by Brown et al (2014), who had previously demonstrated the utility of this technique in Chenopodium . Lugol's Stain is a common tool for discriminating between non- waxy (purple-blue) and waxy (red-brown) seeds, for example, in the grain amaranths (Park et al , 2012a, b).…”
Section: Methodsmentioning
confidence: 99%
“…In order to amplify and sequence the ends of GBSSI, we employed a rapid amplification of complementary DNA (cDNA) ends (RACE) strategy (Yeku and Frohman, 2011) using the SMARTer RACE cDNA Amplification Kit (Clontech, Mountain View, CA, USA), following the manufacturer's protocol. The mRNA for this procedure was extracted from immature inflorescences (green and pre-anthesis) collected from C. quinoa and C. berlandieri plants as described in Brown et al (2014). The inflorescences were immediately frozen in liquid nitrogen and subsequently stored at − 80°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 2017 ) Granule-bound starch synthase I Physicochemical properties of starch Amylose content Brown et al. ( 2015 ) 4 Amaranth Cytochrome P450 , 4,5-DOPA dioxygenase extradiol 1 Natural pigments for food, cosmetic and medicine industry Betalain content Lightfoot et al. ( 2017 ) Aspartate kinase 1 and dihydrodipicolinate synthase Key enzymes of amino acid biosynthetic pathways Lysine content Clouse et al.…”
Section: Deriving Innovations In the Traditional Mixed Cropping Systementioning
confidence: 99%